Pharmacokinetic and clinical effects of two bupivacaine concentrations on axillary brachial plexus block - Ferraro,Leonardo H.C. (2018)
Abstract Introduction: The risk of systemic bupivacaine toxicity is a persistent problem, which makes its pharmacokinetic study fundamental for regional anesthesia safety. There is little evidence of its influence on plasma peak at different concentrations. The present study compares two bupivacaine concentrations to establish how the concentration affects this drug plasma peak in axillary brachial plexus block. Postoperative latency and analgesia were also compared. Methods: 30 patients were randomized. In the 0.25% Group, 0.25% bupivacaine (10 mL) was injected per nerve. In the 0.5% Group, 0.5% bupivacaine (5 mL) was injected per nerve. Peripheral blood samples were collected during the first 2 h after the blockade. For sample analyses, high performance liquid chromatography mass spectrometry was used. Results: Plasma peak occurred 45 min after the blockade, with no difference between groups at the assessed time-points. Plasma peak was 933.97 ± 328.03 ng.mL−1 (mean ± SD) in 0.25% Group and 1022.79 ± 253.81 ng.mL−1 in 0.5% Group (p = 0.414). Latency was lower in 0.5% Group than in 0.25% Group (10.67 ± 3.71 × 17.33 min ± 5.30, respectively, p = 0.004). No patient had pain within the first 4 h after the blockade. Conclusion: For axillary brachial plexus block, there was no difference in bupivacaine plasma peak despite the use of different concentrations with the same local anesthetic mass. The concentration inversely influenced latency.